Fluvial architectural style and stacking patterns in a high-accommodation coal-bearing succession: the upper Permian Newcastle Coal Measures, eastern Australia - Christopher R. Fielding; Stephen McLoughlin; Chris Mays; Allen P. Tevyaw; Tracy D. Frank (International Journal of Coal Geology, 2025)

Assessing South Africa’s marine protected area quality and progress towards conservation goals: An application of The MPA Guide framework - Laurel C. Field; Kendyl Wright; Jenna Sullivan-Stack; Jean M. Harris; Stephen P. Kirkman; Peter J. Fielding; Ané Oosthuizen; Siyabonga Dlulisa; Anastasiya Laznya; Emanuel J. Gonçalves; Kirsten Grorud-Colvert (Marine Policy, 2025)

Public opinion about solar radiation management: A cross-cultural study in 20 countries around the world - Nadja Contzen; Goda Perlaviciute; Linda Steg; Sophie Charlotte Reckels; Susana Alves; David Bidwell; Gisela Böhm; Marino Bonaiuto; Li-Fang Chou; Victor Corral-Verdugo; Federica Dessi; Thomas Dietz; et al. (Climatic Change, 2024)
Some argue that complementing climate change mitigation measures with solar radiation management (SRM) might prove a last resort to limit global warming to 1.5 °C. To make a socially responsible decision on whether to use SRM, it is important to consider also public opinion, across the globe and particularly in the Global South, which would face the greatest risks from both global warming and SRM. However, most research on public opinion about SRM stems from the Global North. We report findings from the first large-scale, cross-cultural study on the public opinion about SRM among the general public ( N = 2,248) and students ( N = 4,583) in 20 countries covering all inhabited continents, including five countries from the Global South and five ‘non-WEIRD’ (i.e. not Western, Educated, Industrialised, Rich, and Democratic) countries from the Global North. As public awareness of SRM is usually low, we provided participants with information on SRM, including key arguments in favour of and against SRM that appear in the scientific debate. On average, acceptability of SRM was significantly higher in the Global South than in the ‘non-WEIRD’ Global North, while acceptability in the ‘WEIRD’ Global North was in between. However, we found substantial variation within these clusters, especially in the ‘non-WEIRD’ Global North, suggesting that countries do not form homogenous clusters and should thus be considered individually. Moreover, the average participants’ views, while generally neither strong nor polarised, differed from some expert views in important ways, including that participants perceived SRM as only slightly effective in limiting global warming. Still, our data suggests overall a conditional, reluctant acceptance. That is, while on average, people think SRM would have mostly negative consequences, they may still be willing to tolerate it as a potential last resort to fight global warming, particularly if they think SRM has only minor negative (or even positive) impacts on humans and nature.

The road towards effective governance and management of marine protected areas in South Africa: evolving policies, paradigms and processes - SP Kirkman; P Kowalski; BQ Mann; GM Branch; MG van der Bank; KJ Sink; P Fielding; JB Mann-Lang; MC Pfaff; D Kotsedi; R Adams; S Dlulisa; et al. (African Journal of Marine Science, 2023)

A revised, late Palaeozoic glacial time-space framework for eastern Australia, and comparisons with other regions and events - Christopher R. Fielding; Tracy D. Frank; Lauren P. Birgenheier (Earth-Science Reviews, 2023)

Genomic population structure of Grass Pickerel (Esox americanus vermiculatus) in Canada: management guidance for an at-risk fish at its northern range limit - Nathan K. Lujan; Julia E. Colm; Jason T. Weir; Fielding A. Montgomery; Brice P. Noonan; Nathan R. Lovejoy; Nicholas E. Mandrak (Conservation Genetics, 2022)

Estimating the average distribution of Antarctic krill Euphausia superba at the northern Antarctic Peninsula during austral summer and winter - V. Warwick-Evans; S. Fielding; C. S. Reiss; G. M. Watters; P. N. Trathan (Polar Biology, 2022)
This study was performed to aid the management of the fishery for Antarctic krill Euphausia superba . Krill are an important component of the Antarctic marine ecosystem, providing a key food source for many marine predators. Additionally, krill are the target of the largest commercial fishery in the Southern Ocean, for which annual catches have been increasing and concentrating in recent years. The krill fishery is managed by the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR), which has endorsed a new management framework that requires information about the spatial distribution and biomass of krill. Here, we use krill density estimates from acoustic surveys and a GAMM framework to model habitat properties associated with high krill biomass during summer and winter in the northern Antarctic Peninsula region, an area important to the commercial fishery. Our models show elevated krill density associated with the shelf break, increased sea surface temperature, moderate chlorophyll-a concentration and increased salinity. During winter, our models show associations with shallow waters (< 1500 m) with low sea-ice concentration, medium sea-level anomaly and medium current speed. Our models predict temporal averages of the distribution and density of krill, which can be used to aid CCAMLR’s revised ecosystem approach to fisheries management. Our models have the potential to help in the spatial and temporal design of future acoustic surveys that would preclude the need for modelled extrapolations. We highlight that the ecosystem approach to fisheries management of krill critically depends upon such field observations at relevant spatial and temporal scales.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Will COVID-19 change the way we teach medical physics post pandemic? - A. Haworth; A. L. Fielding; S. Marsh; P. Rowshanfarzad; A. Santos; P. Metcalfe; R. Franich (Physical and Engineering Sciences in Medicine, 2020)

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

The potential role of Antarctic krill faecal pellets in efficient carbon export at the marginal ice zone of the South Orkney Islands in spring - A. Belcher; G. A. Tarling; C. Manno; A. Atkinson; P. Ward; G. Skaret; S. Fielding; S. A. Henson; R. Sanders (Polar Biology, 2017)

Controls over Ocean Mesopelagic Interior Carbon Storage (COMICS): Fieldwork, Synthesis, and Modeling Efforts - Richard J. Sanders; Stephanie A. Henson; Adrian P. Martin; Tom R. Anderson; Raffaele Bernardello; Peter Enderlein; Sophie Fielding; Sarah L. C. Giering; Manuela Hartmann; Morten Iversen; Samar Khatiwala; Phyllis Lam; et al. (Frontiers in Marine Science, 2016)

Rootless cone eruption processes informed by dissected tephra deposits and conduits - P. Reynolds; R. J. Brown; T. Thordarson; E. W. Llewellin; K. Fielding (Bulletin of Volcanology, 2015)

Seabed foraging by Antarctic krill: Implications for stock assessment, bentho‐pelagic coupling, and the vertical transfer of iron - Katrin Schmidt; Angus Atkinson; Sebastian Steigenberger; Sophie Fielding; Margaret C. M. Lindsay; David W. Pond; Geraint A. Tarling; Thor A. Klevjer; Claire S. Allen; Stephen Nicol; Eric P. Achterberg (Limnology and Oceanography, 2011)
A compilation of more than 30 studies shows that adult Antarctic krill ( Euphausia superba ) may frequent benthic habitats year‐round, in shelf as well as oceanic waters and throughout their circumpolar range. Net and acoustic data from the Scotia Sea show that in summer 2‐20% of the population reside at depths between 200 and 2000 m, and that large aggregations can form above the seabed. Local differences in the vertical distribution of krill indicate that reduced feeding success in surface waters, either due to predator encounter or food shortage, might initiate such deep migrations and results in benthic feeding. Fatty acid and microscopic analyses of stomach content confirm two different foraging habitats for Antarctic krill: the upper ocean, where fresh phytoplankton is the main food source, and deeper water or the seabed, where detritus and copepods are consumed. Krill caught in upper waters retain signals of benthic feeding, suggesting frequent and dynamic exchange between surface and seabed. Krill contained up to 260 nmol iron per stomach when returning from seabed feeding. About 5% of this iron is labile, i.e., potentially available to phytoplankton. Due to their large biomass, frequent benthic feeding, and acidic digestion of particulate iron, krill might facilitate an input of new iron to Southern Ocean surface waters. Deep migrations and foraging at the seabed are significant parts of krill ecology, and the vertical fluxes involved in this behavior are important for the coupling of benthic and pelagic food webs and their elemental repositories.

A transposon insertion single-gene knockout library and new ordered cosmid library for the model organism Streptomyces coelicolor A3(2) - L. T. Fernández-Martínez; R. Del Sol; M. C. Evans; S. Fielding; P. R. Herron; G. Chandra; P. J. Dyson (Antonie van Leeuwenhoek, 2011)

Advanced InSAR atmospheric correction: MERIS/MODIS combination and stacked water vapour models - Zhenhong Li; E. J. Fielding; P. Cross; R. Preusker (International Journal of Remote Sensing, 2009)

Variants of the CD40 ligand gene are not associated with increased susceptibility to tuberculosis in West Africa - Sarah J. Campbell; Pardis Sabeti; Katherine Fielding; Jackson Sillah; Boubacar Bah; Per Gustafson; Kebba Manneh; Ida Lisse; Giorgio Sirugo; Richard Bellamy; Steve Bennett; Peter Aaby; et al. (Immunogenetics, 2003)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)